Is healthcare really equal for all? Assessing the horizontal and vertical equity in healthcare utilisation among older Ghanaians - Vincent Dei; Miguel San Sebastian (BMC, 2018)
Abstract Background There is a lack of focused research on the older population in Ghana and about issues pertaining to their access to healthcare services. Furthermore, information is lacking regarding the fairness in the access to these services. This study aimed to ascertain whether horizontal and vertical equity requirements were being met in the healthcare utilisation among older adults aged 50 years and above. Methods This study was based on a secondary cross-sectional data from the World Health Organization's Study on global AGEing (SAGE) and adult health wave 1 conducted from 2007 to 2008 in Ghana. Data on 4304 older adults aged 50 years-plus were analysed. Bivariate and multivariable analyses were carried out to analyse the association between outpatient/inpatient utilisation and (1) socioeconomic status (SES), controlling for need variables (horizontal equity) and (2) need variables, controlling for SES (vertical equity). Odds ratios with 95% confidence intervals were calculated to analyse the association between relevant variables. Results Horizontal and vertical inequities were found in the utilisation of outpatient services. Inpatient healthcare utilisation was both horizontally and vertically equitable. Women were found to be more likely to use outpatient services than men but had reduced odds of using inpatient services. Possessing a health insurance was also significantly associated with the use of both inpatient and outpatient services. Conclusion Whilst equity exists in inpatient care utilisation, more needs to be done to achieve equity in the access to outpatient services. The study reaffirms the need to evaluate both the horizontal and vertical dimensions in the assessment of equity in healthcare access. It provides the basis for further research in bridging the healthcare access inequity gap among older adults in Ghana.